Fulvic acid-iron colloid promotes the migration of As(III) in porous media - Yanhao Li; Youru Yao; Xinyi Wang; Huimin Zhang; Fengman Fang; Yuesheng Lin; Zhiming Zhang; Qing Ji; Jia Yu (Journal of Contaminant Hydrology, 2026)

Mantle melting and magma ocean dynamics on Mercury impacted by sulfur in reduced mafic magmas - Xiaofeng Lu; Olivier Namur; Yongjiang Xu; Bernard Charlier; Yanhao Lin (Earth and Planetary Science Letters, 2026)

Revisiting zircon-melt REE partitioning systematics: new insight into shallow crustal melting on early Earth - Sheng Shang; Haoxiong He; Wim van Westrenen; Fraukje M. Brouwer; Yanhao Lin (Geochimica et Cosmochimica Acta, 2026)

Electropositive interface engineering accelerates start-up and enhances nitrate removal in microbial electrochemical denitrification systems (MEDS) - Jiannan Li; Yanhao Deng; Yijie Lin; Yanfang Song; Ye Qiu; Guohong Liu; Yujie Feng (Journal of Environmental Management, 2026)

Supplementary irrigation alleviates the inhibition effect of warming on metallic micronutrients absorption - Haifang Pang; Shangying Ma; Fengni Xue; Zongzhen Li; Junjie Hu; Zeyu Xin; Yongzhe Ren; Yanhao Lian; Tongbao Lin; Zhiqiang Wang (European Journal of Agronomy, 2026)

Emerging tire additives and their quinone derivatives in marine species: Characteristics, sources, and health risks - Yiqing Xing; Shuping Tan; Shuaidan Chang; Xiaoqin Lin; Peixuan Li; Jiong Liu; Tao Zhou; Ji-Chang Zhou; Yanhao Zhang; Chunxue Yang (Journal of Hazardous Materials, 2026)

Concentrated mannan oligosaccharide supports grass carp (Ctenopharyngodon idellus) health during Ichthyophthirius multifiliis infection: Histopathological and immunological study - Fulong Li; Ming Xu; Baipeng Chen; Senyue Liu; Yanhao Cao; Yufan Zhang; Gang Lin; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Ceramic fiber aerogels based flexible solar steam generators enabling efficient thermal localization and high salt resistance - Yun Jiang; Yumin Liu; Lin Li; Zhibin Li; Pengzhang Li; Xianshu Qiao; Wenyan Zhao; Chuanjin Tian; Weiwei Sun; Yanhao Dong; Zhipeng Xie; Chang-An Wang (Desalination, 2025)

The role of sulfur on the liquidus temperature and olivine-orthopyroxene equilibria in highly reduced magmas - Fabrizio Saracino; Bernard Charlier; Yishen Zhang; Manon Lécaille; Yanhao Lin; Olivier Namur (Chemical Geology, 2025)

High-pressure Raman spectroscopy of Al-rich and pure-Mg phase D - Chaowen Xu; Li Zhang; Xiaofeng Lu; Yanhao Lin; Shuo Qu; Shuchang Gao; Fengxia Sun; Ying Li (Physics and Chemistry of Minerals, 2025)

Diamide insecticides in PM2.5: The unreported rural and urban air pollutants - Yanhao Zhang; Zifang Peng; Peiru Luo; Lin Zhu; Qingyun He; Congcong Pei; Dan Yin; Wenfen Zhang; Shusheng Zhang; Zongwei Cai (Journal of Hazardous Materials, 2025)

Non-Henrian behavior of hydrogen in plagioclase – basaltic melt partitioning - Yongjiang Xu; Yanhao Lin; Haiyan Zheng; Wim van Westrenen (Chemical Geology, 2024)

Raman spectroscopic study of liebenbergite and Ni2SiO4 spinel at high pressure and high temperature: nickel effects on the vibration properties of olivine and spinel structures - Shuchang Gao; Jinpu Liu; Hang Cheng; Li Zhang; Yanhao Lin; Xiaoguang Li; Xueqing Qin (Physics and Chemistry of Minerals, 2024)

Renewable biomass reinvigorates sustainable water-energy nexus - Hongxu Chen; Jiatao Xu; Zhiyong Jason Ren; Hailong Lin; Leli Zhang; E. Reaihan; Yanhao Yuan; Zihan Wang; Zhidan Liu (Science Bulletin, 2024)

Insights into pollution characteristics and human health risks of plasticizer phthalate esters in shellfish species - Xiaoqin Lin; Luanxun Lin; Shuaidan Chang; Yiqing Xing; Yanhao Zhang; Chunxue Yang (Science of The Total Environment, 2024)

Multi-omics analysis of attenuated variant reveals potential evaluation marker of host damaging for SARS-CoV-2 variants - Guangshan Xie; Lin Zhu; Siwen Liu; Cun Li; Xin Diao; Yanhao Zhang; Xiuli Su; Yuanyuan Song; Guodong Cao; Li Zhong; Pui Wang; Xiaojuan Liu; et al. (Science China Life Sciences, 2024)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

MiR-145 alleviates Hcy-induced VSMC proliferation, migration, and phenotypic switch through repression of the PI3K/Akt/mTOR pathway - Minghao Zhang; Fan Li; Xiuyu Wang; Jian Gong; Yushan Xian; Guan Wang; Zihan Zheng; Chenxu Shang; Bo Wang; Yanhao He; Weirong Wang; Rong Lin (Histochemistry and Cell Biology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)